Peran Notaris dalam Mencegah Penyalahgunaan Perwalian pada Perbuatan Hukum Anak di Bawah Umur - Karmila Sari Sukarno (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the forms of guardianship abuse in legal acts involving minors and to examine the role of notaries in preventing such abuse based on Law Number 2 of 2014 concerning the Position of Notary. Guardianship is essentially a legal instrument intended to protect the personal interests and property of children who lack legal capacity to perform legal acts, yet the authority granted to guardians is prone to being abused. This study employs a normative legal research method with a statutory approach, supported by primary and secondary legal materials. The results show that guardianship abuse generally occurs in three forms: unilateral control over a child's property, transfer of a child's property beyond the guardian's authority, and negligence by the guardian resulting in loss. The role of notaries in preventing such abuse is realized through examining the legality of a guardian's authority before drafting an authentic deed, namely by verifying the legal basis of the guardianship status, assessing whether the exercise of authority genuinely serves the child's best interests, and ensuring that the guardian's actions remain within legal bounds as a manifestation of the precautionary principle. Nevertheless, this preventive role has not been optimally integrated with guardianship oversight institutions such as the Balai Harta Peninggalan (Orphan's Chamber), so that stronger regulation and inter-institutional oversight synergy are needed to achieve optimal legal protection for minors.